A Preliminary Genome-Wide Association Study of Pain-Related Fear: Implications for Orofacial Pain - Cameron L. Randall; Casey D. Wright; Jonathan M. Chernus; Daniel W. McNeil; Eleanor Feingold; Richard J. Crout; Katherine Neiswanger; Robert J. Weyant; John R. Shaffer; Mary L. Marazita (Pain Research and Management)
Background. Acute and chronic orofacial pain can significantly impact overall health and functioning. Associations between fear of pain and the experience of orofacial pain are well-documented, and environmental, behavioral, and cognitive components of fear of pain have been elucidated. Little is known, however, regarding the specific genes contributing to fear of pain. Methods. A genome-wide association study (GWAS; N=990) was performed to identify plausible genes that may predispose individuals to various levels of fear of pain. The total score and three subscales (fear of minor, severe, and medical/dental pain) of the Fear of Pain Questionnaire-9 (FPQ-9) were modeled in a variance components modeling framework to test for genetic association with 8.5 M genetic variants across the genome, while adjusting for sex, age, education, and income. Results. Three genetic loci were significantly associated with fear of minor pain (8q24.13, 8p21.2, and 6q26; p<5×10-8 for all) near the genes TMEM65, NEFM, NEFL, AGPAT4, and PARK2. Other suggestive loci were found for the fear of pain total score and each of the FPQ-9 subscales. Conclusions. Multiple genes were identified as possible candidates contributing to fear of pain. The findings may have implications for understanding and treating chronic orofacial pain.